Bycatch in the South African midwater trawl fishery for horse mackerel (Trachurus capensis) as established from observer records - Reed, Jodie Romay (Department of Biological Sciences, 2016)
The South African midwater trawl fishery targets adult horse mackerel (Trachurus capensis) on the Agulhas Bank. The bulk of the catch is taken by a single midwater trawler. The bycatch of this fishery is investigated by analysing observer records from 2004 to 2014 to report on bycatch composition, volumes and temporal and spatial patterns. Small fauna were analysed by extrapolation of sample weights and large fauna were counted. The midwater trawl fishery was estimated to have caught 25 415 t annually, with a bycatch rate of 6.9% of the total catch, by weight. Bycatch species with the highest average annual catches were chub mackerel (Scomber japonicus), redeye roundherring (Etrumeus whiteheadi), ribbonfish (Lepidopus caudatus) and hake (Merluccius spp.). Large fauna bycatch species included Cape fur seals (Arctocephalus pusillus), sharks (15 species), sunfish (Mola mola) and cetaceans (two species). Temporal analysis revealed significant differences between day-time and night-time CPUE for nine species, and significant differences in seasonal CPUE for 17 species. Spatial analysis of small fauna species composition and of large fauna species composition identified three groups in each. The 100% observer coverage is high compared to other South African fisheries, and, although the average sampling rate of 1.56% is low, an increase in the sampling rate might not be feasible owing to the size of catches. The bycatch rate in this fishery is low compared to other South African trawl fisheries but similar to global midwater trawl bycatch rates. There are species overlaps with various fisheries, namely the demersal trawl, small pelagic, linefishery, shark longline and squid fisheries, yet the total catch estimates from this fishery are generally small relative to catches taken in the target fisheries.